Nurses perception to the implementation of therapeutic communication in intensive care unit - Neny Ariyanti; Sri Suparti (UM Purwokerto Press, 2020)
Therapeutic communication in intensive rooms was a therapeutic communication initiated by nurses to patients with intensive conditions whichrequired critical thinking, fast and precise measures in coping with each patient's needs. To figure out the nurses’ perceptions of the application of therapeutic communication in Intensive room.The study was qualitative phenomenological study, involving eight intensive care nurses participants from IGD, HCU, ICU and NICU. The inclusion criteria were nurses who had worked at least 1 year in the intensive unit, with a minimum education level of bachelor in nursing, through in-depth interviews. The data were analyzed using the Colaizzi method. There were 4 themes identified in the nurses’ perception of the application of therapeutic communication: communication to help the healing process, adaptation and information, stages, technical and benefits of communication. The communication which had not been widely explored wasthe one to help the patients' adaptation process to illness and the communication in emergency situations. The therapeutic communication model is adjusted to the goals and characteristics of patients. Especially for the patients in emergency condition, the nurses are required to have sensitivity and communication skills which have not been sufficiently explored. The communication tends to be directional, not interactive, while the non-verbal communication has not been carried out optimally.